2018
DOI: 10.1101/gad.318436.118
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 regulation of the key adaptor protein NCoR1 is critical for γ-globin gene repression

Abstract: Human globin gene production transcriptionally "switches" from fetal to adult synthesis shortly after birth and is controlled by macromolecular complexes that enhance or suppress transcription by cis elements scattered throughout the locus. The DRED (direct repeat erythroid-definitive) repressor is recruited to the ε-globin and γ-globin promoters by the orphan nuclear receptors TR2 (NR2C1) and TR4 (NR2C2) to engender their silencing in adult erythroid cells. Here we found that nuclear receptor corepressor-1 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…It should be noted that we cannot formally exclude involvement of corepressors other than NCOR and SMRT in PT-S264-dependent repression. Genetic deletion of NCOR1 was unsuccessful in our hands; this is consistent with the notions that NCOR function may be necessary for regulation of the cell cycle (91), genome stability (92), or other critical processes (62). Cellular models without this limitation or knock-in approaches might be suitable to resolve whether NCOR and SMRT complexes are sufficient for repression by PPARβ/δ inverse agonists.…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that we cannot formally exclude involvement of corepressors other than NCOR and SMRT in PT-S264-dependent repression. Genetic deletion of NCOR1 was unsuccessful in our hands; this is consistent with the notions that NCOR function may be necessary for regulation of the cell cycle (91), genome stability (92), or other critical processes (62). Cellular models without this limitation or knock-in approaches might be suitable to resolve whether NCOR and SMRT complexes are sufficient for repression by PPARβ/δ inverse agonists.…”
Section: Discussionsupporting
confidence: 87%
“…BAP1 was shown to deubiquitinate HCF-1 at the N-terminus, which is essential for BAP1 binding and BAP1-dependent cell growth inhibition 10 . Other epigenetic/transcription factors such as Krueppel-like factor 5 (KLF5) 37 , chromatin-remodeling ATPase INO80 38 , DNA methyltransferase 1 (DNMT1) 39 , nuclear receptor corepressor-1 (NCoR1) 40 , peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α) 41 , and type 3 inositol-1,4,5-trisphosphate receptor (IP3R3) 42 are all identified as BAP1 unique non-histone substrates (Fig. 2D ).…”
Section: The Functions Of the Bap1 Complex At The Chromatin Levelmentioning
confidence: 99%
“…ChIP. ChIP assays were conducted as described previously 26 . Table 1) and verified by Sanger sequencing.…”
Section: Hplcmentioning
confidence: 99%
“…We previously reported that TR2/TR4 directly binds to the g-globin promoter to recruit a multimeric Direct Repeat Erythroid-Definitive (DRED) multi-subunit protein complex to repress g-globin transcription in adult erythroid cells 21,22 . The core co-repressor subunits of both the DRED complex and BCL11a include a scaffold protein, NCoR1, which recruits the epigenetic chromatin modifying enzymes DNMT1 and LSD1, among several others [25][26][27] . LSD1/KDM1A is a flavin adenine dinucleotide-dependent histone demethylase that is specific for methylated histone H3 lysine 4 and 9 (H3K4 and H3K9) 28,29 .…”
Section: Introductionmentioning
confidence: 99%